Perencanaan keselamatan, kontrol keselamatan dan kinerja keselamatan - Gutomo, Ardhianto (Jurnal Proyek Teknik Sipil, 2024)
Abstract: Despite the fact that lean construction (LC) has been shown to increase construction safety, little research has been done been carried out to investigate how LC technology can be applied to safety management. This the study aims to close this gap by developing a safety planning and control (SPC) process based on LC technology and evaluate it using a structural equation model. The process is based on the final planner system research framework (LPS) and consists of four sub-systems (ie, analysis layer, planning layer, control layer, and performance layer). Data was collected from 150 projects HSE employee at building construction in the Jakarta area. These findings will serve as a guide for construction stakeholders looking to improve efficiency safety management by incorporating some LC technology into the SPC process. And four subsystems work together to create a positive circulation system that aids long-term improvement construction safety management.